Evaluasi Kebijakan Publik dalam Transformasi Ujian SIM dengan Pendekatan Evidence Based dan Teori U - Prasetiyo, Anggy (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
This study evaluates the policy of eliminating zig-zag and figure 8 tests in two-wheeled vehicle practice for Class C Driving License in Indonesia, which is based on the Evidence-Based Policy approach and Theory U. This policy aims to improve the relevance and effectiveness of the test in measuring driving skills on the highway. Empirical data shows that the zig-zag and figure 8 tests are not relevant to real driving situations and often cause failure of test takers who actually have adequate skills. By replacing them with more realistic tests such as evasion simulations and sudden braking, this policy has succeeded in increasing the pass rate of test takers and reducing psychological stress. The application of Theory U in the policy-making process also allows for active participation from the community, academics, and safety experts, so that this policy is more responsive and adaptive to field needs. This study concludes that an evidence-based and collaborative approach can produce policies that are more relevant, fair, and effective in improving road safety.